Commentary: The complexity of family dynamics in child anxiety disorders — a commentary on Breinholst et al. (2018). Issue 1 (3rd December 2018) - Domoney, Jill; Nath, Selina
Abstract : Breinholst et al. explore the impact of parental behaviour and parent–child attachment on child anxiety disorders. They show that maternal variables did not predict child anxiety, while insecure attachment to the father was a significant contributor. But can we really say it's down to dad? The importance of including fathers in both research and clinical work on child anxiety disorders certainly needs to be highlighted, but family dynamics are complex, and we need careful study designs which can capture some of this complexity in order to shed light on the most important targets for intervention.